Analysis of the Positive Arctic Oscillation Index Event and Its Influence in the Winter and Spring of 2019/2020 - Zhang, Jie; Sheng, Zheng; Ma, Yantong; He, Yang; Zuo, Xinjie; He, Mingyuan (Frontiers in Earth Science, 2021)
There were continuous positive Arctic Oscillation index (AOI) and large-scale weather and climate anomalies in the Northern Hemisphere in the winter and spring of 2019/2020, and the relationship between these anomalies is an important issue for sub-seasonal to seasonal (S2S) predictability. This article shows that an AOI event with splitting characteristics occurred in the Northern Hemisphere and that there was a gap between the periods in event, which has not been observed in any of the 12 previous positive AOI events. The 3 stages of upward propagating planetary wave (UPPW) variation caused the gap between the periods. First, in early November, the westerly flow from the troposphere to the stratosphere weakened, resulting in persistent weak UPPWs that allowed a strong polar vortex to form. Then, the 2 strong UPPWs in January and early February caused the original westerlies to decelerate and induced warming in the lower stratosphere. However, the UPPWs caused only moderate changes in the geopotential height and temperature due to the strong polar vortex that had formed in the previous stage. This moderate AOI decline resulted in the conditions that divided the positive event into 2 periods. Finally, the low-level westerlies became stronger and strengthened the UPPWs into the stable stratosphere, which ended the second positive AOI period in late March. The role of zonal circulation anomalies (ZCA) in the upper stratosphere as metrics of and intermediates in UPPW-AO interactions is revealed in this paper. The typical ZCA development mode was identified by statistical analysis and a composite treatment based on 8 historical positive AOI events. In this mode, when strong UPPWs occur and lead to the consequent propagation of the ZCA from the stratosphere to the troposphere, the geopotential height field in the lower troposphere changes away from a typical AO mode; eventually, the AOI becomes abnormal. The temperature anomaly and ZCA produced in the 2 positive AOI periods during the winter and spring of 2019/2020 led to increasing precipitation in the eastern polar region, northern Asia and areas along 60°N latitude.